2019
DOI: 10.1002/ijc.32425
|View full text |Cite
|
Sign up to set email alerts
|

Sp1‐mediated epigenetic dysregulation dictates HDAC inhibitor susceptibility of HER2‐overexpressing breast cancer

Abstract: Human epidermal growth factor receptor 2 (HER2/erbB2) is a key driver and therapeutic target for breast cancer. The treatment of HER2‐positive breast cancer remains a clinical challenge largely due to the limited understanding of HER2‐driving oncogenic signaling and the frequent resistance to simply HER2‐targeted therapy. Here, we show that the histone deacetylase inhibitor, trichostatin A (TSA), suppresses HER2‐overexpressing breast cancer via upregulation of miR‐146a and the resultant repression of its oncog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…46,47 The relative expression of Sp1 in cancer cells in several tumor models, including colon cancer, breast cancers, esophageal carcinomas, and pulmonary cancers, has been shown to be higher than that of neighboring normal tissue. [48][49][50] Previous trials showed that 65% of patients with lung cancer had a greater amount of Sp1 in tumor tissues, 51 and that malignant LUAD cells expressed greater concentrations of Sp1 mRNA and protein relative to ordinary bronchial epithelial cells. 52 Overall, it has been demonstrated that Sp1 contributes to tumorigenesis by controlling growth and proliferationrelated gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 The relative expression of Sp1 in cancer cells in several tumor models, including colon cancer, breast cancers, esophageal carcinomas, and pulmonary cancers, has been shown to be higher than that of neighboring normal tissue. [48][49][50] Previous trials showed that 65% of patients with lung cancer had a greater amount of Sp1 in tumor tissues, 51 and that malignant LUAD cells expressed greater concentrations of Sp1 mRNA and protein relative to ordinary bronchial epithelial cells. 52 Overall, it has been demonstrated that Sp1 contributes to tumorigenesis by controlling growth and proliferationrelated gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Sp1 in most cases promotes gene expression; however, miR‐326 was negative regulated by Sp1. Previous study suggested that Sp1 not only functions as a transcription factor, but also participates in epigenetic modification by recruiting HDACs 23,24 . In renal cell carcinoma, loss of the Sp1‐HDAC1 complex is associated with elevated histone H3 acetylation at GM2‐synthase gene promoter, resulting in increased expression of GM2‐synthase and faster proliferation of tumour 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In the murine system, transcription factor Sp1 binds to a 39 bp region of CD34 that lies upstream of CD34 transcription initiation start site and increased the promoter activity in hematopoietic cells and in Sp1 null Drosophila S2 cells . Sp1 transcription factor, in fact, gets activated by phosphorylation and reportedly enhances the aggressiveness of breast cancer cells, gliomas, non–small cell lung cancer and pancreatic cancer to name a few. In other words, the binding of SP1 to CD34 promoter or promoters of other genes is associated with enhanced stemness.…”
Section: Cd34—a Dynamic Moleculementioning
confidence: 99%